Successful treatment with thalidomide for pemphigus vulgaris - Zhang, Bingjie; Mao, Xuming; Zhao, Wenling; Jin, Hongzhong; Li, Li (Therapeutic advances in chronic disease, 2020)
Background: Pemphigus vulgaris (PV) is a potentially life-threatening mucocutaneous autoimmune blistering disease characterized by suprabasal acantholysis, causing painful mucocutaneous blisters and erosions. Current mainstay therapy for pemphigus is systemic corticosteroids in combination with or without immunosuppressive adjuvants, which may cause severe adverse effects and seriously impact on the quality of life in pemphigus patients. The objective of this study was to evaluate the efficacy and safety of thalidomide therapy in patients with PV. Methods: This study examined six PV patients from June 5, 2017, to November 11, 2018, in the dermatology department of Peking Union Medical College Hospital. Treatment with thalidomide was applied at a dose of 50–100 mg/day for disease control. Results: The mean age of the six patients (two male and four female patients) at the time of thalidomide therapy initiation was 50.2 years (range: 38–67 years), and the total duration of follow-up after thalidomide therapy was 13.2 months (range: 5–25 months). All patients responded favorably to thalidomide treatment, and three patients showed a dramatic reduction in anti-Dsg3 autoantibodies in the serologic examinations within 1 year. Five patients were found to have mucosal involvement. Mild adverse effects were noted in three patients, which could be managed after the application of symptomatic treatment and did not interfere with the pemphigus therapy. Conclusion: These results demonstrate that thalidomide could be an effective and safe option for PV patients, especially those who are concerned about steroid-induced severe complications, and have mucosal diseases.